Nanocomposite polysulfone membranes with improved antifouling properties - Dzhodzhyk, Oleg; Kolesnyk, Iryna; Konovalova, Viktoria; Burban, Anatoliy (My University, 2016)
The immobilization methods of nanoparticles of magnetite and tin oxide on membrane surface have been developed for improving the stability of polysulfone membrane to fouling. SnO2 nanoparticles were deposited on the membrane by the method of "layer-by-layer" with using polyelectrolyte complexes of polyethyleneimine and carboxymethyl cellulose to provide them photocatalytic properties. Fe3O4 nanoparticles were covalently immobilized on the membrane using polyethyleneimine as a polymer spacer. It has been shown that the resulting nanocomposite membranes were characterized by improved transport properties in the ultrafiltration of protein solutions. Membrane resistance to fouling increased by reducing the effect of concentration polarization and increasing mass transfer coefficient. З метою покращення стійкості полісульфонових мембран до забруднення розроблені методи іммобілізації наночастинок оксиду стануму та магнетиту на їх поверхні. Наночастинки SnO2 наносили на мембрану методом “layer-by-layer” з використанням поліелектролітного комплексу поліетиленімін карбоксиметилцелюлоза для надання їм фотокаталітичних властивостей. Наночастинки Fe3O4 були іммобілізовані на мембрані ковалентно за допомогою полімерного спейсеру поліетиленіміну. Показано, що отримані нанокомпозитні мембрани характеризуються покращеними транспортними властивостями у процесі ультрафільтрації білків. Стійкість мембран до забруднення збільшується за рахунок зменшення ефекту концентраційної поляризації та зростання коефіцієнту масопереносу.
Keywords: nanocomposite membrane; membrane fouling; membrane modification; нанокомпозитні мембрани; модифікування мембран; забруднення мембран